Geographic information systems: their use in environmental epidemiologic research...reprinted from Environmental Health Perspectives, Public Health Service, U.S. Department of Health and Human Services, June 1997, Vol. 105, No. 6 - Vine MF; Degnan D; Hanchette C (Journal of Environmental Health, 1998)
Advances in geographic information system (GIS) technology, developed by geographers, provide new opportunities for environmental epidemiologists to study associations between environmental exposures and the spatial distribution of disease. A GIS is a powerful computer mapping and analysis technology capable of integrating large quantities of geographic (spatial) data as well as linking geographic with nongeographic data (e.g., demographic information, environmental exposure levels). In this paper, we provide an overview of some of the capabilities and limitations of GIS technology; we illustrate, through practical examples, the use of several functions of a GIS, including automated address matching, distance functions, buffer analysis, spatial query, and polygon overlay; we discuss methods and limitations of address geocoding, often central to the use of a GIS in environmental epidemiologic research; and we suggest ways to facilitate its use in future studies. Collaborative efforts involving epidemiologists, biostatisticians, environmental scientists, GIS specialists, and medical geographers are needed to realize the full potential of GIS technology in environmental health research and may lead to innovative solutions to complex questions.